2008
DOI: 10.1179/174313208x276240
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of third ventricle dilation in spontaneous intracerebral hemorrhage: a preliminary clinical study

Abstract: Although the roles of various factors are well described in the prognosis of spontaneous ICH, little is known about the role of third ventricle dilation. Based on our results, we concluded that third ventricle dilation is a poor prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…23 Interestingly, development of shuntdependent hy drocephalus was more likely in those patients with a tha lamic hemorrhage, but independent of other hemorrhage locations or IVH volume, despite the fact that IVH is known to predict worse outcomes in patients with ICH in a volumedependent manner. 18,25 Given the anatomical relationship of thalamic hemorrhages to the third ven tricle and the foramen of Monro, it is intuitive that he matoma formation in this location more easily results in obstruction of CSF flow independent of IVH volume than in hemorrhages occurring in other locations. Reports of thalamic cavernomas and hemorrhages without intraven tricular extension have documented the development of hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…23 Interestingly, development of shuntdependent hy drocephalus was more likely in those patients with a tha lamic hemorrhage, but independent of other hemorrhage locations or IVH volume, despite the fact that IVH is known to predict worse outcomes in patients with ICH in a volumedependent manner. 18,25 Given the anatomical relationship of thalamic hemorrhages to the third ven tricle and the foramen of Monro, it is intuitive that he matoma formation in this location more easily results in obstruction of CSF flow independent of IVH volume than in hemorrhages occurring in other locations. Reports of thalamic cavernomas and hemorrhages without intraven tricular extension have documented the development of hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…A strong association of IVH in the third and fourth ventricle with poor outcome has been described previously [23,24]. It seems that both local mechanical and biochemical factors contribute to the unfavorable course.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, blood volume in the fourth ventricle showed a trend towards influence on prognosis, while total IVH volume and IVH volume in the lateral ventricles were not associated with outcome. Involvement of the third and fourth ventricles has already been shown to be a negative prognostic predictor in ICH with IVH 3 5 6. However, a volume dependent relationship between initial ventricular haemorrhage in the third ventricle and outcome has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the prognostic value of blood volume in the different parts of the ventricular system, particularly in the third and fourth ventricles located within the brainstem structures with high eloquence. Very few studies have investigated in detail the role of IVH with third and fourth ventricle involvement as a cause of morbidity 3 5 6. Two retrospective case series of approximately 20 patients each have suggested that dilation of the third5 and fourth6 ventricles is associated with worse outcome and high mortality in patients with IVH secondary to spontaneous ICH, especially when obstructive hydrocephalus due to casting of the aqueduct is present 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation